2023
DOI: 10.3390/ijerph20043347
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatizing Monkeypox and COVID-19: A Comparative Framing Study of The Washington Post’s Online News

Abstract: Background: Stigma relating to health can result in a broad range of vulnerabilities and risks for patients and healthcare providers. The media play a role in people’s understanding of health, and stigma is socially constructed through many communication channels, including media framing. Recent health issues affected by stigma include monkeypox and COVID-19. Objectives: This research aimed to examine how The Washington Post (WP) framed the stigma around monkeypox and COVID-19. Guided by framing theory and sti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Some health workers demonstrated a positive attitude 35,47 displaying a willingness to care for mpox patients and adherence to infection prevention and control measures. 27,37 However, other studies reported negative attitudes, such as fear, stigmatization, [48][49][50] and refusal to care for mpox patients. 51 Satisfactory attitude towards mpox was observed in less than a third (30.7%) of Lebanon healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…Some health workers demonstrated a positive attitude 35,47 displaying a willingness to care for mpox patients and adherence to infection prevention and control measures. 27,37 However, other studies reported negative attitudes, such as fear, stigmatization, [48][49][50] and refusal to care for mpox patients. 51 Satisfactory attitude towards mpox was observed in less than a third (30.7%) of Lebanon healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…Although mpox can affect anyone, a notable characteristic of this outbreak was that it was overwhelmingly (i.e., more than 90%) concentrated among SMM (i.e., gay, bisexual, and other men who have sex with men; Philpott et al, 2022). Because of this demographic trend in mpox cases, media narratives and public health communications have, in some cases, uncritically associated mpox with SMM (Ju et al, 2023; UNAIDS, 2022). This has led to widespread concerns by researchers, public health officials, advocacy groups, and some members of the public that the outbreak would intensify the stigma faced by SMM (e.g., Banjar & Alaqeel, 2024; Bergman et al, 2022; Keum et al, 2023; Lee & Morling, 2022; Logie, 2022; März et al, 2022; Mazzagatti & Riva, 2022; Ng et al, 2022; Sah et al, 2022; UNAIDS, 2022).…”
mentioning
confidence: 99%